Impact of ethical climate, moral distress, and moral sensitivity on turnover intention among haemodialysis nurses: a cross-sectional study - Haengsuk Kim; Hyunjung Kim; Younjae Oh (BMC, 2023)
Abstract Background While several studies have been performed on turnover intention among nurses, limited studies have considered the ethical perspectives on turnover intention among haemodialysis nurses. The purpose of this study was to clarify the impact of ethical factors, namely ethical climate, moral distress, and moral sensitivity on turnover intention among haemodialysis nurses. Methods This cross-sectional research was conducted between July and August 2017. A total of 148 haemodialysis nurses were invited to participate in the study by convenience sampling from 11 general and university hospitals in South Korea. Data were analysed using SPSS for t-test, one-way analysis of variance, Pearson's correlation coefficients, and multiple regression analysis. Results In the final regression model, the adjusted R-squared significantly explained 34.6% of the variance in turnover intention (F = 22.534, p < .001) when moral distress related to physician practice (β = 0.310, p = .001) and ethical climate related to the hospital climate (β = − 0.253, p = .003) and manager (β = − 0.191, p = .024) were included. Following the stepwise multiple regression process, all subdomains related to moral sensitivity were excluded due to no statistical significance in the final regression model. Conclusion To reduce turnover intention among haemodialysis nurses, hospitals and managers should pay attention to haemodialysis nurses' moral distress originating from physicians' practice and improve their ethical climate. Additionally, it is required that the impact of moral sensitivity on turnover among nurses working in diverse care settings be examined further.